Modern dose-finding designs for cancer phase I trials : drug combinations and molecularly targeted agents /: drug combinations and molecularly targeted agents. ([2018]) - Hirakawa, Akihiro; Satō, Hiroyuki; Daimon, Takashi; Matsui, Shigeyuki
No abstract available